Effectiveness of Tempe Biscuits and Honey to Decrease Frequency of Stools in Children Diarrhea - Nurwahidah Nurwahidah; Arbianingsih Arbianingsih (State Islamic University of Sunan Ampel, 2019)
Frequency of stools in diarrhea children requires special attention because it can cause dehydration which is the leading cause of death in children with diarrhea. Previous studies state that tempe and honey are effective in reducing the frequency of stools in diarrhea children. However, it is not known which intervention is more effective. Therefore, this study aims to determine whether there is a difference in the effectiveness of tempe biscuits and honey to decrease the frequency of stools in diarrhea. This study employed the quasi-experiment design with two groups pre and post-test. A total of 30 samples were taken by Accidental Sampling. Samples were divided into 2 groups, where 15 people were given the intervention of tempe biscuits, and 15 other people were given honey. Giving tempe biscuits and honey are given 3 times a day for two consecutive days. Data were analyzed using the Wilcoxon Test. The results of this study indicate that tempe biscuits and honey is effective in reducing the frequency of stools in diarrhea children (p = 0.001 and p<0,001). Although the decrease in the frequency of stools in the group with honey was greater than the group with tempe biscuits, the results of this study showed that there were no significant differences between the two interventions to decrease the frequency of stools (p = 0.385). Therefore, in reducing the frequency of defecation, tempe biscuit and honey can be used as good food supplements for diarrhea children.